Size-selective purification of hepatitis B virus-like particle in flow-through chromatography: types of ion exchange adsorbent and grafted polymer architecture - Hon, Wei Ng; Fu, Micky Xiang Lee; Gek, Kee Chua; Gan, Bee Koon; Tan, Wen Siang; Chien, Wei Ooi; Siah, Ying Tang; Eng, Seng Chan; Beng, Ti Tey (Wiley, 2018)
Hepatitis B virus-like particles expressed in Escherichia coli were purified using anion exchange adsorbents grafted with polymer poly(oligo(ethylene glycol) methacrylate) in flow-through chromatography mode. The virus-like particles were selectively excluded, while the relatively smaller sized host cell proteins were absorbed. The exclusion of virus-like particles was governed by the accessibility of binding sites (the size of adsorbents and the charge of grafted dextran chains) as well as the architecture (branch-chain length) of the grafted polymer. The branch-chain length of grafted polymer was altered by changing the type of monomers used. The larger adsorbent (90 μm) had an approximately twofold increase in the flow-through recovery, as compared to the smaller adsorbent (30 μm). Generally, polymer-grafted adsorbents improved the exclusion of the virus-like particles. Overall, the middle branch-chain length polymer grafted on larger adsorbent showed optimal performance at 92% flow-through recovery with a purification factor of 1.53. A comparative study between the adsorbent with dextran grafts and the polymer-grafted adsorbent showed that a better exclusion of virus-like particles was achieved with the absorbent grafted with inert polymer. The grafted polymer was also shown to reduce strong interaction between binding sites and virus-like particles, which preserved the particles' structure.